At the intersection between toxicology and physiology: What we have learned about sea lampreys and bony fish physiology from studying the mode of action of lampricides - Birceanu, Oana; Tessier, Laura R.; Huerta, Belinda; Li, Weiming; McDonald, Allison; Wilkie, Michael P. (Journal of Great Lakes Research, 2021)
The lampricides 3-trifluoromethyl-4-nitrophemol (TFM) and niclosamide have been used for over 60 years to control the invasive sea lamprey (Petromyzon marinus) population in the Laurentian Great Lakes. In this review, we summarize these findings in the context of the mode of action of both lampricides, with a focus on: (1) the physiology of uptake, bodily distribution and mode of action, detoxification, and excretion of lampricides in lamprey and non-target fishes, (2) the development of an Adverse Outcome Pathway for TFM and niclosamide, and (3) the identification of novel avenues for future research that can be further explored to ensure continuous suppression of the sea lamprey population in the Great Lakes. We explored how research on the mode of action of lampricides has provided novel insights into the gill microenvironment and how this impacts lampricide toxicity; described new information on mitochondria and tissue physiology; and discussed how the activity of enzymes that are involved in detoxification pathways impacts the response of fishes to xenobiotics. Considering the information that has been generated over the years on sea lamprey and bony fish physiology from studying the mode of action of lampricides, here we propose an Adverse Outcome Pathway for TFM and niclosamide and identify novel avenues for research on the short and long-term effects of lampricide applications, either alone or in combination. Lastly, we discuss how the differences in physiology between sea lampreys and non-target fishes can be further exploited to ensure continuous suppression of the sea lamprey population in the Great Lakes.
Keywords: Invasive species; Lampricides; Niclosamide; Physiology; TFM; dept.che; peer-reviewed